2008
DOI: 10.2139/ssrn.1310756
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship by Circumstances and Abilities: The Mediating Role of Job Satisfaction and Moderating Role of Self-Efficacy

Abstract: Prior studies have found that job dissatisfaction and self-efficacy are significant factors influencing individuals' entrepreneurial propensity. Existing literature on entrepreneurship often regards job dissatisfaction as an entrepreneurial push factor and self-efficacy as an entrepreneurial pull factor. The argument is that individuals who are dissatisfied with their jobs are more likely to seek alternative mode of employment such as self-employment. In other words, poor job circumstances may push individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…These scales tap into some underlying motivational characteristics of the entrepreneur. The motivational concept of “mastery” has a great deal in common with the concept of self‐efficacy, which is a key antecedent of entrepreneurial intentions (Bandura and Locke 2003; Krueger, Reilly, and Carsrud 2000; Wong, Lee, and Leung 2006; Zhao, Seibert, and Hills 2005). Self‐efficacy is one example of where motivation has been assumed in entrepreneurial intentions research but not directly and empirically studied.…”
Section: Motivation and The Entrepreneurmentioning
confidence: 99%
“…These scales tap into some underlying motivational characteristics of the entrepreneur. The motivational concept of “mastery” has a great deal in common with the concept of self‐efficacy, which is a key antecedent of entrepreneurial intentions (Bandura and Locke 2003; Krueger, Reilly, and Carsrud 2000; Wong, Lee, and Leung 2006; Zhao, Seibert, and Hills 2005). Self‐efficacy is one example of where motivation has been assumed in entrepreneurial intentions research but not directly and empirically studied.…”
Section: Motivation and The Entrepreneurmentioning
confidence: 99%
“…Despite contested merits of incubators (Chan & Lau, 2005), the analysis (Wong et al, 2006) reveals that the resources of a business incubator have a strong positive effect for innovative small ventures. This is consistent with the World Bank's study that business incubators have positive effects both for creating viable, innovative, highgrowth enterprises and for the broader innovation and entrepreneurship ecosystem (Khalil & Olafsen, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The incubator centre can provide a nourishing environment for business and technological assistance; however, there is much evidence of a high failure rate among incubated ventures. One reason for this failure is that the incubatees overestimate their personal strengths while underestimating their weaknesses (Wong et al, 2006). In this study, need for achievement, locus of control, and risk-taking propensity are represented as key entrepreneurial personalities.…”
Section: Entrepreneurial Personalitymentioning
confidence: 96%
See 1 more Smart Citation
“…Ajzen (1991), Mwiya, Wang, Shikaputo, Kaulungombe, andKayekesi (2017), andPaço, Ferreira, Raposo, Rodrigues, andDinis (2011) have confirmed that perceived behavioral control predicts entrepreneurial intention. Lortie and Castogiovanni (2015), Urban and Pendame (2015), and Wong, Lee, and Leung (2006) strongly believed that perceived behavioral control could acts as the strongest predictor as compared to the subjective norm and attitude towards the behavior. For instance, research confirms that strong financial support could affect the success of business initiation (Gimmon & Levie, 2010).…”
Section: Perceived Behavioral Controlmentioning
confidence: 99%